The positioning of English as a key skill in the labour market of Marseille’s Tourist Office - WILSON, ADAM (International Journal of Language, Translation and Intercultural Communication, 2018)
Marseille is reinventing itself as an urban tourist destination. The aim of this paper is to explore the effects that the resulting intensification of international tourism may have on the city, its population and its labour market. Drawing on previous research, language is shown to be a powerful lens through which to explore such phenomena. Therefore, an ethnographic research project was undertaken in Marseille’s Tourist Office, focussing on language use in encounters between international tourists and tourist advisers. The analyses of these data presented here show that English facilitates communication between these parties and thus becomes an indispensable resource for those working at the Tourist Office. It is thus shown how the English language is a key skill in the Tourist Office’s labour market and acts as a discriminatory factor in the recruitment of tourism professionals. In conclusion, some of the potential wider social repercussions are discussed.